THE CHEF PASTRY PERFORMANCE AT THE ZURI HOTEL PEKANBARU - Bella Sri Novita; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The city of Pekanbaru has a good tourism potential, with a strategic location and abundant culture, especially in the rapidly growing hospitality sector. This research aims to determine the responsibility of a pastry chef in carrying out excellent quality performance while working. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The informants in this study were Exc chef, Sous chef and Demi chef. In this research, the data collection techniques used were interviews, observation and documentation. The results of this research is affirming the quality of the chef pastry performance in making products, accuracy at work, strategies in building a good conduct, the delays at work, damage to the product produced and the amount of work produced for the sake of improving the quality of excellent performance on pastry chefs at The Zuri Hotel PekanbaruKeywords: Performance, Chef, Pastry,